2017
DOI: 10.1007/s11010-017-3230-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of the new methoxy-stilbenes on expression of receptors and enzymes involved in estrogen synthesis in cancer breast cells

Abstract: Our previous study showed that the new synthetic methoxy-stilbenes, 3,4,2′-trimethoxy-trans-stilbene (3MS), 3,4,2′,4′-tetramethoxy-trans-stilbene (4MS), and 3,4,2′,4′,6′-pentamethoxy-trans-stilbene (5MS), modulate the constitutive expression of enzymes and receptors involved in estrogen metabolism in breast immortalized epithelial MCF10 cells. In this study, we evaluated the effect of 3MS, 4MS, and 5MS in comparison to resveratrol activity in MCF7 estrogen-dependent and MDA-MB-231 estrogen-independent breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Our previous studies also showed that 3,5,4ʹ-tri-MS caused a massive accumulation of cells at the G2/M phase of the cell cycle and increased the apoptosis rate related to p53 induction in rat C6 glioma cells [13]. In addition, synthetic 3,4,2′-tri-MS, 3,4,2′,4′-tetra-MS, and 3,4,2′,4′,6′-penta-MS modulated the constitutive expression of enzymes and receptors involved in estrogen metabolism in breast normal and cancer cells more efficiently than RSV [14,15]. Cytochromes P450 1A1 and 1B1 are crucial for the metabolism of estrogen to their reactive electrophilic forms.…”
Section: Introductionmentioning
confidence: 96%
“…Our previous studies also showed that 3,5,4ʹ-tri-MS caused a massive accumulation of cells at the G2/M phase of the cell cycle and increased the apoptosis rate related to p53 induction in rat C6 glioma cells [13]. In addition, synthetic 3,4,2′-tri-MS, 3,4,2′,4′-tetra-MS, and 3,4,2′,4′,6′-penta-MS modulated the constitutive expression of enzymes and receptors involved in estrogen metabolism in breast normal and cancer cells more efficiently than RSV [14,15]. Cytochromes P450 1A1 and 1B1 are crucial for the metabolism of estrogen to their reactive electrophilic forms.…”
Section: Introductionmentioning
confidence: 96%
“…Promoters I.3 and II are the major promoters directing aromatase expression in breast cancer, and genistein may inhibit the activities of promoters I.3 and II for CYP19 regulation (Chen et al, 1999 ). A study showed that a methoxy derivative of resveratrol, 3MS, could efficiently inhibit the expression of aromatase protein encoded by CYP19 in MDA-MB- 231 cells (Licznerska et al, 2017 ). The standard GBE (EGb 761) significantly inhibited aromatase activity and reduced the expression of CYP19 mRNA and CYP19 promoter I.3 and PII (Park et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…They reduced receptor expression and also suppressed the expression of the CYP19 gene more effectively than resveratrol. The synthetic stilbenes were more powerful inhibitors of cell proliferation and promoters of apoptosis . Over a decade ago Saberi et al synthesises several 1‐[(benzofuran‐2‐yl)phenylmethyl]‐pyridine, ‐imidazole, and ‐triazole compounds and noted that the 6‐methoxy‐ and 6‐hydroxy‐substituted benzofuran derivatives were highly effective inhibitors of CYP19 far more effective and selective than the parent compound; overall the effects were comparable with that of anastrozole.…”
Section: Molecular Configuration and Antitumour Efficacy Of Analoguesmentioning
confidence: 99%
“…The synthetic stilbenes were more powerful inhibitors of cell proliferation and promoters of apoptosis. 37 Over a decade ago Saberi et al 38 synthesises several 1-[(benzofuran-2-yl) phenylmethyl]-pyridine, -imidazole, and -triazole compounds and noted that the 6-methoxy-and 6-hydroxysubstituted benzofuran derivatives were highly effective inhibitors of CYP19 far more effective and selective than the parent compound; overall the effects were comparable with that of anastrozole. Methoxy substitution of the coumarin core produces potent aromatase inhibitors, possibly not comparable in bioactivity to anastrozole or letrozole, but distinctly more potent than aminoglutethimide.…”
Section: Molecular Configuration and Antitumour Efficacy Of Analoguesmentioning
confidence: 99%